2014
DOI: 10.1182/blood-2014-06-583765
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of first salvage treatment in CLL patients treated initially with FCR (fludarabine, cyclophosphamide, rituximab)

Abstract: Key Points Patients who relapse within 3 years of frontline FCR therapy have poor survival when treated with conventional salvage regimens. Such patients are suitable for allogeneic stem cell transplantation and novel noncytotoxic therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 18 publications
5
68
0
3
Order By: Relevance
“…The importance of a long PFS and achieving a (clinical) CR are consistent with the findings both of Tam et al (2014), who showed that patients treated with FCR with a first‐line PFS longer than 3 years survive better in the long‐term than those with PFS <3 years, and also of the VISTA (Velcade ® as Initial Standard Therapy in Multiple Myeloma) trial in multiple myeloma, in which a CR either after initial therapy or after relapse was equally associated with longer OS (Harousseau et al , 2010). …”
Section: Discussionsupporting
confidence: 90%
“…The importance of a long PFS and achieving a (clinical) CR are consistent with the findings both of Tam et al (2014), who showed that patients treated with FCR with a first‐line PFS longer than 3 years survive better in the long‐term than those with PFS <3 years, and also of the VISTA (Velcade ® as Initial Standard Therapy in Multiple Myeloma) trial in multiple myeloma, in which a CR either after initial therapy or after relapse was equally associated with longer OS (Harousseau et al , 2010). …”
Section: Discussionsupporting
confidence: 90%
“…The study aim was to assess the feasibility and efficacy of remission-induction chemotherapy followed by alloSCT. The sample size calculation was based on the assumptions that 2-year PFS of patients fitting the entry criteria was~25% without alloSCT at the time this study started 17,24,[30][31][32][33][34][35] and that protocol treatment would result in 2-year PFS of at least 45% from registration, which resulted in 41 required patients (for details see Supplementary Material). All analyses were intention to treat, restricted to eligible patients.…”
Section: Statistical Considerations and Methodsmentioning
confidence: 99%
“…[1][2][3] Though the majority of CLL patients receiving FCR as frontline therapy are destined to relapse, a subgroup of cases may experience a durable first remission. [4][5][6][7][8] In the new scenario of targeted agents for CLL, 9-14 affordable treatment strategies should be patient-risk oriented, as well as cost-effective and resource-saving. [15][16][17] On this basis, there is an increasing interest in identifying a priori patients who may maximally benefit from FCR.…”
Section: Introductionmentioning
confidence: 99%
“…The follow-up of our cohort does not equate that of the seminal FCR series, [4][5][6][7][8] and the retrospective design of our study represents an inevitable limitation. Nevertheless, an external validation of our data are provided by the consistent description of patients in durable remission in clinical trials of FCR-treated CLL, and by the individual association between PFS and the status of 17p, 11q, or IGHV by multivariable analyses from prospective cohorts.…”
mentioning
confidence: 99%